The Pastoral Search Journey: A Guide to Finding Your Next Pastor - Vonhof, John (Rowman & Littlefield Publishers, 2010)
Most churches have sought out a new pastor many times, yet search committees often feel as though they are inventing the process from scratch. In The Pastoral Search Journey, John Vonhof provides detailed guidance for search committees to ensure a good match between pastor and congregation. This is Vonhof's third book about the pastoral search -- but the first to discuss interim pastors, transitions between pastors, and the use of the Internet and digital media. Vonhof advises congregational leaders on establishing the search committee; ensuring the congregation is cared for during the pastoral vacancy; conducting the congregational self-study and creating an information packet; finding, communicating with, and interviewing candidates; determining selection criteria as well as evaluating and recommending candidates; managing call negotiations; and finally welcoming the congregation s new pastor. Sample letters, forms, and other tools are provided.